Using Facial Recognition Tools for Health Assessment. Issue 2 (April 2021) - Boczar, Daniel; Avila, Francisco R.; Carter, Rickey E.; Moore, Pamela A.; Giardi, Davide; Guliyeva, Gunel; Bruce, Charles J.; McLeod, Christopher J.; Forte, Antonio Jorge
Abstract : The number of applications for facial recognition technology is increasing due to the improvement in image quality, artificial intelligence, and computer processing power that has occurred during the last decades. Algorithms can be used to convert facial anthropometric landmarks into a computer representation, which can be used to help identify nonverbal information about an individual's health status. This article discusses the potential ways a facial recognition tool can perform a health assessment. Because facial attributes may be considered biometric data, clinicians should be informed about the clinical, ethical, and legal issues associated with its use.